Caring for patients with end‐stage renal disease during COVID‐19 lockdown: What (additional) challenges to family caregivers?. Issue 1 (28th March 2021) - Sousa, Helena; Frontini, Roberta; Ribeiro, Oscar; Paúl, Constança; Costa, Elísio; Amado, Leonilde; Miranda, Vasco; Ribeiro, Fernando; Figueiredo, Daniela
Abstract: Introduction: Caring for a patient with end‐stage renal disease undergoing in‐centre haemodialysis can be a stressful experience, likely to involve significant burden. Within the context of the new coronavirus pandemic, these patients are highly vulnerable to infection by COVID‐19, which might increase the care demands and burden of family caregivers. Aim: This study aimed to explore the subjective experiences of family caregivers of non‐COVID‐19 patients with end‐stage renal disease undergoing in‐centre haemodialysis during the COVID‐19 lockdown. Study design: A qualitative study was performed with a purposive sample. Methods: Semi‐structured telephone interviews were conducted with 19 family caregivers (50.7 ± 14 years old) of patients undergoing in‐centre haemodialysis in April 2020. Findings: Four major themes were identified: (1) emotional distress; (2) changes in caregiving responsibilities; (3) educational and supportive needs; and (4) coping strategies to deal with the outbreak and with the lockdown. Discussion: The findings suggest that family caregivers of patients undergoing in‐centre haemodialysis have to manage several additional care responsibilities due to COVID‐19 lockdown. The dialysis team should consider the development of educational and supportive interventions to meet family caregivers' needs, mitigate emotional distress, fears and concerns, and prevent caregiver burden during the COVID‐19 pandemic.